2023
DOI: 10.1093/ofid/ofad526
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Response to Dolutegravir Plus Lamivudine in People With Suppressed Human Immunodeficiency Virus Type 1 and Historical M184V/I: A Systematic Literature Review and Meta-analysis

Madhusudan Kabra,
Tristan J Barber,
Clotilde Allavena
et al.

Abstract: Background To investigate the impact of the M184V/I mutation on virologic response to dolutegravir (DTG) + lamivudine (3TC) in suppressed-switch populations, a meta-analysis was performed using virologic outcomes from people with HIV-1 (PWH) with and without M184V/I before DTG + 3TC switch in real-world studies identified via systematic literature review. Sensitivity analyses were performed using data from PWH with M184V/I in interventional studies identified via targeted literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…These outcomes are consistent with observations from a systematic literature review and meta-analysis that consisted of 5 real-world evidence–based studies and 5 interventional trials, including TANGO and SALSA, of individuals who were ART experienced and had switched to DTG/3TC while having M184V/I mutations previously detected by historical RNA or archived proviral DNA [ 17 ]. Overall, the systematic literature review showed a low prevalence of M184V/I before the switch to DTG/3TC in the evidence-based studies (11% [264/2428]) and low proportions of virologic failure postswitch among those with historical M184V/I in both the evidence-based studies (week 24, 1.43% [3/210]; week 48, 3.45% [9/261]; week 96, 3.81% [8/210]) and the interventional trials (week 24, 0% [0/42]; week 48, 0% [0/97]; week 96, 0% [0/38]).…”
Section: Discussionsupporting
confidence: 83%
“…These outcomes are consistent with observations from a systematic literature review and meta-analysis that consisted of 5 real-world evidence–based studies and 5 interventional trials, including TANGO and SALSA, of individuals who were ART experienced and had switched to DTG/3TC while having M184V/I mutations previously detected by historical RNA or archived proviral DNA [ 17 ]. Overall, the systematic literature review showed a low prevalence of M184V/I before the switch to DTG/3TC in the evidence-based studies (11% [264/2428]) and low proportions of virologic failure postswitch among those with historical M184V/I in both the evidence-based studies (week 24, 1.43% [3/210]; week 48, 3.45% [9/261]; week 96, 3.81% [8/210]) and the interventional trials (week 24, 0% [0/42]; week 48, 0% [0/97]; week 96, 0% [0/38]).…”
Section: Discussionsupporting
confidence: 83%
“…Of note, 1 individual with M184V detected in their baseline resistance test achieved virologic suppression by week 6 [71]. A meta-analysis of people living with HIV who switched to DTG + 3TC reported low estimated proportions with VF based on data from real-world cohorts at weeks 24, 48, and 96 regardless of the presence of pre-switch M184V/I mutations (with M184V/I: 0.01, 0.03, and 0.04, respectively; without M184V/I, 0.00, 0.02, and 0.02, respectively), which were consistent with estimated proportions with VF in participants with historical M184V/I from interventional studies (0.00, 0.00, and 0.00, respectively) [72]. Rates of VF were also infrequent 24 weeks after first-line initiation of DTG + 3TC (n = 106) or DTG + TDF/XTC (n = 108) without baseline resistance testing in the randomized phase 4 D2ARLING trial, where no RAMs were observed at VF for the 1 participant taking DTG + TDF/XTC who experienced VF [73].…”
Section: Discussionsupporting
confidence: 79%